Biochemistry, structure, and cellular internalization of a four nanobody‐bearing Fc dimer. (17th June 2021) - Chabrol, Eric; Fagnen, Charline; Landron, Sophie; Marcheteau, Estelle; Stojko, Johann; Guenin, Sophie‐Pénélope; Antoine, Mathias; Fould, Benjamin; Ferry, Gilles; Boutin, Jean A.; Vénien‐Bryan, Catherine
Abstract: VHH stands for the variable regions of heavy chain only of camelid IgGs. The VHH family forms a set of interesting proteins derived from antibodies that maintain their capacity to recognize the antigen, despite their relatively small molecular weight (in the 12, 000 Da range). Continuing our exploration of the possibilities of those molecules, we chose to design alternative molecules with maintained antigen recognition, but enhanced capacity, by fusing four VHH with one Fc, the fragment crystallizable region of antibodies. In doing so, we aimed at having a molecule with superior quantitative antigen recognition (×4) while maintaining its size below the 110 kDa. In the present paper, we described the building of those molecules that we coined VHH2 ‐Fc‐VHH2 . The structure of VHH2 ‐Fc‐VHH2 in complex with HER2 antigen was determined using electronic microscopy and modeling. The molecule is shown to bind four HER2 proteins at the end of its flexible arms. VHH2 ‐Fc‐VHH2 also shows an internalization capacity via HER2 receptor superior to the reference anti‐HER2 monoclonal antibody, Herceptin®, and to a simple fusion of two VHH with one Fc (VHH2 ‐Fc). This new type of molecules, VHH2 ‐Fc‐VHH2, could be an interesting addition to the therapeutic arsenal with multiple applications, from diagnostic to therapy.